A Review on Multifunctional Carbon-Dots Synthesized From Biomass Waste: Design/ Fabrication, Characterization and Applications - Khairol Anuar, Nurul Kamilah; Tan, Huey Ling; Lim, Ying Pei; So’aib, Mohamad Sufian; Abu Bakar, Noor Fitrah (Frontiers in Energy Research, 2021)
Carbon-Dots (C-Dots) have drawn much attention in recent years owing to their remarkable properties such as high biocompatibility, low toxicity, nano-scale size, and ease of modification with good tuneable photoluminescence performance. These unique properties have led C-Dots to become a promising platform for bioimaging, metal ion sensing and an antibacterial agent. C-Dots can be prepared using the top-down and bottom-up approaches, in which the latter method is commonly used for large scale and low-cost synthesis. C-Dots can be synthesized using sustainable raw materials or green biomass since it is environmentally friendly, in-expensive and most importantly, promotes the minimization of waste production. However, using biomass waste to produce high-quality C-Dots is still a matter of concern waiting for resolution, and this will be the main focus of this review. Fundamental understanding of C-Dots such as structure analysis, physical and chemical properties of C-Dots, various synthesis methodology and type of raw materials used are also discussed and correlated comprehensively. MoreoverAdditionally, factors affecting the bandgap of the C-Dots and the strategies to overcome these shortcomings are also covered. Moreover, formation mechanism of C-Dots focusing on the hydrothermal method, option and challenges to scale up the C-Dots production are explored. It is expected that the great potential of producing C-Dots from agricultural waste a key benefit in view of their versatility in a wide range of applications.